Sentencing for Minors in Sexual Abuse Cases - Subroto, Devy Wahyuningtyas; Susila, Muh Endriyo (Universitas Muhammadiyah Yogyakarta, 2020)
Sexual abuse is committed not only by adults but also by minors. The legal process upon children who have committed sexual abuse refers to the Law Number 11 of 2012 on the Juvenile Court System. The purpose of this study is to find out the factors to be considered by the panel of judges in imposing penalty upon the perpetrators. The study employs both normative and empirical approaches. It is found with regard to the liability issue, the panel of judges relies on both juridical and non- juridical consideration. In sexual abuse case that was tried in Kebumen District Court, beside imposing imprisonment, the panel of judges also ordered the perpetrators to undergo work training as a substitute of fine.